DIRI RELIGIUS: SUATU PERSPEKTIF PSIKOLOGI TERHADAP KEPRIBADIAN AKHLAQUL KARIMAH - Retno Hanggarani Ninin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
Akhlaqul karimah in general is a temperament that contains elements of goodness. The characteristics consistent with morals, ethics, morality, dignity, and kindness in accordance with reference to the Quran and the Sunnah of the Prophet Muhammad. From psychologycal perspective, “self” is the aggregate related. Defined as an awareness of one’s own unique existence, self is the crucial factor of regulatory and control functions over the thoughts, feelings, motives, and behavior. Accordingly, the proposed concept “religious self” can be defined as an awareness of the one’s own existence in relation to God,in which the awareness of the relationship will be the critical factor that regulate and control the thoughts, feelings, motives, and behavior. Religious self is being argued as having four dimensions:Godness belief, awareness of God-self connectednes, acceptance of God's willpowertoward them, and motif of obedience to God’s order. In term of akhlaqul karimah, each dimension of religious self is analogous to the concept of iman (faith), ikhsan (feel of being observed by the Divine), tawakal (resignation), and taqwa (piety), which are features indicate the quality of akhlaqul karimah. Critical review of concepts in common psychology ie religiosity, spirituality, personality, and self, offers new conceptualisation of akhlaqul karimah by the way of psychology.